2020
DOI: 10.3389/fphys.2020.00140
|View full text |Cite
|
Sign up to set email alerts
|

Selected Amino Acids Promote Mouse Pre-implantation Embryo Development in a Growth Factor-Like Manner

Abstract: Groups of amino acids, and some selected amino acids, added to media used for culture of pre-implantation embryos have previously been shown to improve development in various ways including survival to the blastocyst stage, increased blastocyst cell number and improved hatching. In this study, we cultured 1-cell mouse embryos for 5 days to the hatching blastocyst stage in isosmotic medium (270 mOsm/kg) at high density (10 embryos/10 µL), where autocrine/paracrine support of development occurs, and low density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 47 publications
4
56
0
Order By: Relevance
“…In the derived blastocysts, the cell proliferation, differentiation and death rates were determined using morphological fluorescence staining. To evaluate the possible mechanisms of different responses to insulin, mRNA expression of insulin receptor, insulin-like growth factor I receptor, and selected genes representing two main branches of insulin receptor signaling (phosphatidylinositol 3-kinases [PI3Ks] and mitogen-activated protein kinases [MAPKs] [ 21 , 22 , 23 ]) were analyzed in the blastocysts recovered from control and obese dams using real-time RT-PCR.…”
mentioning
confidence: 99%
“…In the derived blastocysts, the cell proliferation, differentiation and death rates were determined using morphological fluorescence staining. To evaluate the possible mechanisms of different responses to insulin, mRNA expression of insulin receptor, insulin-like growth factor I receptor, and selected genes representing two main branches of insulin receptor signaling (phosphatidylinositol 3-kinases [PI3Ks] and mitogen-activated protein kinases [MAPKs] [ 21 , 22 , 23 ]) were analyzed in the blastocysts recovered from control and obese dams using real-time RT-PCR.…”
mentioning
confidence: 99%
“…The significantly high release of Ala and Gln is consistent with Houghton et al [ 5 ], and inconsistent with Sturmey et al, who declared that mouse embryos at blastocyst stages consumed Gln at a significantly higher rate than the early cleavage stages [ 8 ]. L-Gln is considered to be an essential component of culture media during embryo development over the 2- to 8-cell stages in a number of species [ 24 , 27 ]. It can be metabolized to other AAs (i.e., Glu, Ala, and Asp) [ 28 ] and ATP through the TCA cycle, synthesizes de-novo purine and pyrimidine, protects the embryo against oxidative stress, and acts as an organic osmolyte and a putative regulator in Glc metabolism [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gly, a critical AA for the preimplantation development of both early and late-stage embryos [ 29 ] was also released to the media. Gly is abundant in oviduct fluid [ 29 ], and has been reported to be an essential precursor of polypeptide and nucleic acid synthesis, one of the key organic osmolytes and heavy metal chelators, which undergoes less apoptosis in Gly-cultured embryos [ 8 , 27 , 30 , 31 ]. Tracking the fate of orally administered 15 N-Gly showed that the Gly nitrogen group is mainly transferred to Ser, urea, Gln/Glu, Ala, and other AAs (Leu, Ile, Val, Orn, Pro, and Met) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supplemental L-Pro (50-250 µM) improves proliferation of ESCs (Figure 8; Washington et al, 2010;Casalino et al, 2011), development of pre-implantation embryos (Morris et al, 2020) and fetus survival (Liu et al, 2019). L-Pro is internalized into stem cell cytoplasm through the SLC38A2 (SNAT2) transporter (Tan et al, 2011), and halofuginone (prolyl-tRNA synthetase inhibitor) fully counteracts L-Pro induction of cell proliferation (D'Aniello et al, 2015).…”
Section: Stem Cellsmentioning
confidence: 99%